Comparison of level of mental stress between exercising and non-exercising undergraduate physical therapy students of LUMHS, Jamshoro - Sana Naqi; Kainat Faizan; Fayaz Chandio; Aadil Ameer Ali; Shoaib Waqas; Suhani Bhatti; Aiman Bachani (Archives of Depression and Anxiety - Peertechz Publications, 2021)
Objective: To Compare the Level of Mental Stress among Exercising and Non-Exercising under graduate Physiotherapy Students of LUMHS, Jamshoro. Methodology: A cross sectional survey was conducted from October to December 2019, and the data was collected from the undergraduates students of Institute of Physiotherapy & Rehabilitation Sciences, Liaquat University of Medical and Health Science Jamshoro, Pakistan. The Perceived Stress Scale (PSS) was used among 194 undergraduate physiotherapy students. Apart from the demographics (age, gender, education & locality) the PSS questionnaire consist of 10 questions. The Statistical Package for Social Sciences (SPSS) version 22 was used to interpret the data. Result: The majority (n=101, 51.7%) were from the age group of 18 to 21 years and (n=127, 65.1%) were female. Mostly (n=49, 25.1%) were the students of 1st year Doctor of Physical Therapy and (n=116, 59.4%) of the students were the residents of urban area. Among the non-exercising group of students majority (n=66,68%) were suffering from low level of mental stress, (n=33,34%) were suffering from moderate level of mental stress and (n=24,24.7%) were suffering from severe level of mental stress followed by the exercise group, in which (n=40,41.2%) were suffering from low level of mental stress, (n=21,21.6%) were suffering from moderate level of mental stress and (n=10,10.%) were suffering from severe level of mental stress. Conclusion: The study finalized that the exercising group of students had lower level of mental stress as compare to the non-exercising group of students. However both groups have the individuals with mental stress but the exercising students group had low number of those individuals.